1994
DOI: 10.1104/pp.104.1.271
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Uptake Changes in Ascorbate Free Radical-Stimulated Onion Roots

Abstract: Long-term treatments with ascorbate free radical-stimulated glucose, fucose, sucrose, and nitrate uptake in Allium cepa roots.Clucose and fucose showed saturation kinetics in untreated roots, but after treatment with the ascorbate free radical, uptake was linear with time. Although the rates of nitrate and sucrose uptake increased after treatment with ascorbate free radical, the kinetics were similar to those observed in the controls. Ascorbate and dehydroascorbate inhibited nutrient uptake. l h e uptake rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
20
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 17 publications
2
20
0
Order By: Relevance
“…ASC is a common compound in plants that may be physiologically involved in the regulation of cell-wall extensibility. Our group has published a number of observations that indicate that ASC and its free radical stimulate root elongation and accelerate the quiescence-proliferation transit in onion roots (Hidalgo et al, 1991;De Cabo et al, 1993;González-Reyes et al, 1994b), and similar results are shown in this paper. Onions grown in the presence of ASC had significantly longer roots than onions grown in control conditions; however, DHA inhibited cell elongation, supporting our previously reported data (González-Reyes et al, 1994a).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…ASC is a common compound in plants that may be physiologically involved in the regulation of cell-wall extensibility. Our group has published a number of observations that indicate that ASC and its free radical stimulate root elongation and accelerate the quiescence-proliferation transit in onion roots (Hidalgo et al, 1991;De Cabo et al, 1993;González-Reyes et al, 1994b), and similar results are shown in this paper. Onions grown in the presence of ASC had significantly longer roots than onions grown in control conditions; however, DHA inhibited cell elongation, supporting our previously reported data (González-Reyes et al, 1994a).…”
Section: Discussionsupporting
confidence: 86%
“…On the other hand, ASC or CL treatments decreased both apoplast and cell-wall-bound peroxidase activities, whereas Lyc had a slight stimulating effect. These results are discussed on the basis of a possible control of root elongation by ASC via its action on peroxidases that are involved in the regulation of cell-wall extensibility.ASC and its free radical AFR stimulate the elongation of onion (Allium cepa L.) roots in parallel to a high vacuolization of meristematic cells (Hidalgo et al, 1989;Navas, 1991;González-Reyes et al, 1994b). ASC is required for the progression of the G1 and G2 phases of the cell cycle (Liso et al, 1984).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The region of ROS accumulation in K ϩ -starved roots was similar to the region where antioxidants such as ascorbate and dehydroascorbate accumulated in onion roots under control conditions (44). Increased ascorbate free radicals in this specific region were demonstrated to increase the uptake of sucrose, glucose, and nitrate in onion roots (45). In another study, (46) oxygen-free radicals in Arabidopsis roots were shown to cause a transient increase in K ϩ efflux.…”
Section: Discussionmentioning
confidence: 59%
“…The other hypothesis is that AAO causes the cytoplasm to expand. Monodehydroascorbic acid (MDHA) (a monooxidative species of AsA), which is considered to be the initial one-electron product of AAO activity (DHA forms by disproportionation of MDHA), could accept electrons from a plasma-membrane-bound cytochrome b. Membrane depolarization caused by transmembrane electron transport could stimulate plasma-membrane proton-pump activity (Gonzalez-Reyes et al 1994). Activation of the proton pump stimulates uptake of cellular nutrients and ions.…”
mentioning
confidence: 99%